Current management of premature rupture of the membranes in a preterm pregnancy - Gutiérrez Ramos, Miguel (2018)
The obstetrician and gynecologist must frequently face complicated situations in the practice of obstetrics, one of them is the rupture of the membranes in a preterm pregnancy. While the medical conduct is to preserve both maternal and fetal health, many times the decision may affect fetal health in order to preserve the maternal health. This occurs when the presence of an infection makes it impossible to maintain the normal course of pregnancy and complete gestational age. In many cases the complications that cause prematurity of the newborn will put mother’s life at risk and we must therefore be prepared to minimize the consequences of our decision. In this article we review evidence-based management that the obstetriciangynecologist should consider when this situation occurs.